The Effect of Phaleria macrocarpa Bioactive Fraction (Proliverenol) Supplementation on Liver Damage in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD) - Irsan Hasan; Saut Horas Hatoguan Nababan; Raymond R. Tjandrawinata; Danang Agung Yunaidi; Liana W. Susanto (MEDICINUS, 2025)
Liver is considered one of the most vital organs, acting as the center of metabolism of nutrients and excretion of waste products. Non-alcoholic fatty liver disease (NAFLD) is one of the main causes of chronic liver disease. The management of NAFLD continues to evolve, and clinicians are currently faced with a variety of alternative options, both nonpharmacotherapeutic and pharmacotherapy, to avoid more severe liver disease. Phaleria macrocarpa (Scheff.) Boerl., namely, mahkota dewa in Indonesia, has been used empirically to treat cancer, allergy, and diabetes mellitus. Proliverenolis a proprietary bioactive fraction derived from the dried fruit of Phaleria macrocarpa (Scheff.) Boerl. Proliverenol was reported to have hepatoprotective, anti-inflammatory, antioxidant, and antifibrotic effects. The study found that Proliverenol bioactive fraction, at a dosage of 1000 mg twice daily for at least 4 weeks of treatment, is effective in improving liver damage with a good safety profile.